Brazil - Fortes, Alexandre (Labour/Le Travailleur, 2002)
Abstract In the last two decades, Brazilian unionism and the left have experienced an unprecedented development, posing for the first time in history, a real challenge to the ruling classes. The effects of this new political reality on labour history took a while to be felt, but in recent years a whole new historiography has emerged, leading to the constitution of the Mundos do Trabalho (Worlds of Labour) work group, an official branch of the National History Association.